2007
DOI: 10.1007/s11144-007-5136-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidic and metallic sites on the catalytic performance of Pd/ZSM-5 catalysts in the one-step synthesis of mibk

Abstract: The acidic properties of Pd/ZSM-5 catalysts were characterized by NH 3 -TPD and FT-IR of d 3 -acetonitrile adsorption. Effect of Pd loading on the catalytic activity and product distribution was studied in the one-step synthesis of methyl isobutyl ketone from acetone. The results indicated that a proper balance between acidic and metallic sites was necessary to obtain high catalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…7. 20 In our work, the content of Pd might be too small to cause any inuence on the acidity of ZSM-5. Yang et al had reported that for the ZSM-5 loaded with high Pd content, large Pd particles could block the pores or cover the a Micropore volume is estimated using the t-plot method.…”
Section: Catalyst Characterization and Testsmentioning
confidence: 67%
See 1 more Smart Citation
“…7. 20 In our work, the content of Pd might be too small to cause any inuence on the acidity of ZSM-5. Yang et al had reported that for the ZSM-5 loaded with high Pd content, large Pd particles could block the pores or cover the a Micropore volume is estimated using the t-plot method.…”
Section: Catalyst Characterization and Testsmentioning
confidence: 67%
“…This journal is © The Royal Society of Chemistry 2015 acid sites causing the decrease of acid sites. 20 In our work, the content of Pd might be too small to cause any inuence on the acidity of ZSM-5. Adebajo et al had reported that the catalyst with highly reduced Brönsted acidity could minimize the occurrence of the side reaction of methanol to olens and enhance the methylation of benzene with methanol.…”
Section: Catalyst Characterization and Testsmentioning
confidence: 67%
“…As shown in Figure , all catalysts exhibit two NH 3 desorption peaks at 200–220 and 360–390 °C. Typically, the peak at the lower temperature is attributed to the desorption of NH 3 at weak acid sites, while the peak at the higher temperature corresponds to the desorption from strong acid sites. The adsorption amounts of NH 3 on PdO/ZSM-5 with various Pd-loadings are determined through the deconvolution of the NH 3 -TPD spectra, as presented in Table . After loading of Pd onto ZSM-5, the NH 3 desorption peak from the weak acid sites became less intense.…”
Section: Resultsmentioning
confidence: 99%
“…A number of multifunctional catalysts that were used in one-step conversion of acetone to MIBK have been studied. These catalysts include Pd-ZSM-5 [4], Pd-Zn-Cr mixed oxides [5] and Pd-LDH [6]. High price and easy loss of palladium are the obvious disadvantages.…”
Section: Introductionmentioning
confidence: 99%